Lesiones orales en pacientes de la tercera edad portadores de prótesis dento-muco-soportadas, que acuden al centro Gerontológico Alejandrina Palacios León provincia de Loja cantón Gonzanamá, periodo octubre 2015-junio 2016. - Mendieta Zúñiga, José Luis (2016)
In the geriatric oral rehabilitation prosthetic you can find several alternatives to achieve functional and aesthetic improvement of the patient; but, poor development and manufacture of prostheses cause countless injuries due to their poor development and manufacture of prostheses. The purpose of this study aims to find the most frequent oral lesions suffered by patients seniors Gerontology Center "Alejandrina Palacios Leon" Canton Gonzanamá, which appear when using prostheses dento-muco-supported with prolonged use of the same or being maladaptive, and are products trigger this type of oral mucosa lesions such as Stomatitis, dental épulis, angular cheilitis and oral candidiasis. Data collection was done through of clinical histories of each patient with the help of a set of diagnostic and also a visual examination of both oral mucosa and the state of the prosthesis, a photographic record was made as evidence. The sample was composed up of 60 adults of which 35% (N=21 patients) had Stomatitis subprotesic; 11,67%(N=7p) show the presence of more Stomatitis Dental Epulis subprotesic, 3,33%(N=2p) manifest more Stomatitis subprotesic cheilitis, the 11,67%(N=7p) is characterized with oral candidiasis more Stomatitis subprotesic and finally 38,33% (N=23p) don’t present injuries. It must implement an oral health program for the geriatric patient to avoid these kinds of injuries. Keywords: Oral lesions, Stomatitis, dental épulis, angular cheilitis and oral candidiasis.